SOSCAN: A UNIQUE COMMUNICATION LINK AND INFORMATION SERVICE FOR THE SOCIAL SCIENCES IN CANADA/SOSCAN: UN LIEN DE COMMUNICATION UNIQUE ET UN SERVICE D’INFORMATION POU LES SCIENCES SOCIALES AU CANADA - Knoppers, Jake (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
See PDF